2014
DOI: 10.1111/jop.12268
|View full text |Cite
|
Sign up to set email alerts
|

p‐Akt and its relationship with clinicopathological features and survival in oral squamous cell carcinoma: an immunohistochemical study

Abstract: From these results, the present study suggests that high p-Akt expression found in oral squamous cell carcinoma patients may contribute to tumour growth, metastasis to regional lymph nodes and shorter survival time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 42 publications
3
12
0
2
Order By: Relevance
“…These findings are in line with the overexpression of Akt2 and the phosphorylated form of Akt2 in other cancers and hereditary cancer syndromes, including cancers of the brain, endometrium, ovary, breast, prostate, kidney, colon, lung, thyroid, blood components, glioblastoma, head and neck, neurofibromatosis, tuberous sclerosis, von‐Hippel–Lindau disease, nevoid basal cell carcinoma syndrome, Cowden disease, Peutz‐Jeghers syndrome, familial adenomatous polyposis, and juvenile polyposis . Some studies have shown that Akt2 and p‐Akt overexpression is also associated with poor prognostic parameters of oral cancer, including increased lymph node metastasis, tumor size, and decreased survival rate …”
Section: Discussionsupporting
confidence: 79%
“…These findings are in line with the overexpression of Akt2 and the phosphorylated form of Akt2 in other cancers and hereditary cancer syndromes, including cancers of the brain, endometrium, ovary, breast, prostate, kidney, colon, lung, thyroid, blood components, glioblastoma, head and neck, neurofibromatosis, tuberous sclerosis, von‐Hippel–Lindau disease, nevoid basal cell carcinoma syndrome, Cowden disease, Peutz‐Jeghers syndrome, familial adenomatous polyposis, and juvenile polyposis . Some studies have shown that Akt2 and p‐Akt overexpression is also associated with poor prognostic parameters of oral cancer, including increased lymph node metastasis, tumor size, and decreased survival rate …”
Section: Discussionsupporting
confidence: 79%
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer in the world . Despite advances in the therapeutic approach, the rates of morbidity and mortality of this malignancy have not improved significantly over the past years, with the overall 5‐year survival rate varying between 40% and 60% …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the identification of molecular markers may be a useful tool to identify a lesion's aggressiveness, especially at an early stage. 6,7,8 Ki-67 is expressed in proliferating cells, but quickly disappears when the cell enters into a resting state. This characteristic has stimulated the use of Ki-67 to demonstrate the fraction of proliferating cells in a malignant neoplasm.…”
mentioning
confidence: 99%
“…This characteristic has stimulated the use of Ki-67 to demonstrate the fraction of proliferating cells in a malignant neoplasm. 6,7,9 Another group of proteins that has been recently investigated is the mini-chromosome maintenance proteins (MCM). These proteins are involved in the early stages of eukaryotic genome replication and are believed to serve as a normal component of the replication machinery.…”
mentioning
confidence: 99%